Sistem Perlindungan Model Pendidikan Anak Indonesia dan Thailand Dari Perspektif Hukum dan Kebijakan - Amanda Pratiwi Putri Utomo (Jurnal Hukum Lex Generalis, 2026)
Education is a fundamental right of children as guaranteed by the United Nations Convention on the Rights of the Child (CRC) of 1989 and various national regulations in both Indonesia and Thailand. Although both countries have established legal frameworks governing the protection of children's rights in the education sector, their implementation continues to face significant challenges. This study employs a socio-legal method with a comparative approach between Indonesia and Thailand, supported by literature review, field observations, and in-depth interviews. The data were analyzed qualitatively to identify the conformity between legal norms and the actual practices of child protection within educational environments. The findings reveal that both countries share a commitment to ensuring children's right to education; however, differences exist in the implementation of policies. Thailand demonstrates a more effective implementation through the provision of free education up to upper secondary level and a more integrated educational quality assurance system. In contrast, Indonesia continues to face challenges related to disparities in educational quality, limitations in supporting facilities, and suboptimal supervision of child protection within schools. The study concludes that the effectiveness of child rights protection in the education sector depends not only on the existence of legal regulations but also on the consistency of policy implementation, the quality of educational resources, and sustainable monitoring mechanisms. Therefore, strengthening institutional coordination, enhancing teacher capacity, and developing bilateral cooperation are necessary to support the fulfillment of children's rights to safe, inclusive, and quality education.